2013
DOI: 10.3892/ijo.2013.2218
|View full text |Cite
|
Sign up to set email alerts
|

The pan-histone deacetylase inhibitor LBH589 (panobinostat) alters the invasive breast cancer cell phenotype

Abstract: Abstract. Triple-negative breast cancer (TNBC) is a very aggressive type of tumour and its aggressiveness is linked to E-cadherin downregulation. In estrogen-sensitive breast cancer, high levels of E-cadherin fit with high levels of ERα and MTA3 (a component of the transcription Mi-2/NuRD complex with intrinsic DAC activity). In TNBC the E-cadherin downregulation could be due to epigenetic silencing of the CDH1 gene as well as to the lack of a fully functioning ERα-activated pathway. We report that the pan-his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 42 publications
(52 reference statements)
3
13
0
Order By: Relevance
“…Our previous research and the work presented here demonstrate the ability of the pan-DAC inhibitor LBH589 (Panobinostat) to inhibit the expression of classical EMT-associated genes and induce expression of CDH1 in TNBC cell lines but not in luminal (Table 1) or basal A breast cancer cell lines [11]. These findings are supported by recent work by Fortunati et al that demonstrated LBH589 induction of CDH1 in MDA-MB-231 cells independent of estrogen receptor expression [49]. We also showed LBH589 to be much more potent in its anti-EMT effects than other known HDAC inhibitors, SAHA and TMP269.…”
Section: Discussionsupporting
confidence: 88%
“…Our previous research and the work presented here demonstrate the ability of the pan-DAC inhibitor LBH589 (Panobinostat) to inhibit the expression of classical EMT-associated genes and induce expression of CDH1 in TNBC cell lines but not in luminal (Table 1) or basal A breast cancer cell lines [11]. These findings are supported by recent work by Fortunati et al that demonstrated LBH589 induction of CDH1 in MDA-MB-231 cells independent of estrogen receptor expression [49]. We also showed LBH589 to be much more potent in its anti-EMT effects than other known HDAC inhibitors, SAHA and TMP269.…”
Section: Discussionsupporting
confidence: 88%
“…Another study has confirmed these findings, given that it was found that in MDA-MB231 cells independent of estrogen receptor expression, panobinostat induced CDH1 expression (114). Panobinostat was reported to induce the expression of CDH1 and reduce the migration and invasion of TNBC cells.…”
Section: Hdac Inhibitors As Anti-cancer Agentssupporting
confidence: 69%
“…Vorinostat (suberoylanilide hydroxamic acid, SAHA), the first HDAC inhibitor for refractory and relapsed cutaneous T-cell lymphoma (CTCL) has been approved by FDA [ 45 , 46 ]. LBH589 is a novel pan HDACs inhibitor that possesses potent growth inhibitory activity in Ph(-) ALL cells [ 47 ], triple-negative breast cancer (TNBC)[ 24 ], hepatocellular carcinoma [ 29 ], prostate cancer (PCa) cells [ 48 ], relapsed/refractory Waldenstrom macroglobulinemia (WM) [ 49 ] and multiple myeloma (MM) [ 50 ]. However, to date, the molecular function of LBH589 in WT has remained unknown.…”
Section: Resultsmentioning
confidence: 99%
“…HDAC inhibitor LBH589 has demonstrated antitumor activity, including HDACs suppression and induction of tumor cell apoptosis in various human cancer models. In Triple-negative breast cancer (TNBC), LBH589 has anti-proliferative properties in aggressive breast cancer refractory to hormonal therapy [ 24 ]. In human renal cell carcinoma, LBH589 caused obvious cell cycle arrest in the G2/M phase and caused cell apoptosis [ 25 ].…”
Section: Introductionmentioning
confidence: 99%